CCDSR Learning Model: Innovation in Physics Learning - Iqbal Limatahu; Husni Mubarok (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The purpose of this research is to analyze the validity of the CCDSR learning model. The CCDSR learning model that was developed was validated by 3 experts in a discussion forum commonly called Focus Group Discussion (FGD). The results of the validator assessment indicate that the content and construct validity of the CCDSR learning model are very valid criteria. The valid CCDSR learning model means having several characteristics, namely meeting the need (need), state (the state of the art), having a strong theoretical and empirical foundation, and there is consistency between the components of the model. The CCDSR learning model is included in the criteria of validity, both content and construct so that it can be used as a guide in preparing plans to improve science process skills (SPS) and SPS learning for students of prospective physics teachers.